Correction: Properties and applications of designable and photo/redox dual responsive surfactants with the new head group 2-arylazo-imidazolium. Issue 80 (12th August 2016) - Lin, Changxu; Yang, Long; Xu, Mengchun; An, Qi; Xiang, Zheng; Liu, Xiangyang
Abstract : Correction for 'Properties and applications of designable and photo/redox dual responsive surfactants with the new head group 2-arylazo-imidazolium' by Changxu Lin et al., RSC Adv., 2016, 6, 51552–51561.